The German Generals Talk : Startling Revelations from Hitler's High Command - Liddell Hart, Basil Henry (Rawalpindi Army Education Press, 1979)
Statements made to the author in 1945 by German generals detained as prisoners of war with the author's comments.
Include Maps, Tables and Index.
Keywords: Germany -- World War (1939-1945) -- Military campaigns -- Generals